2019
DOI: 10.1111/raq.12341
|View full text |Cite
|
Sign up to set email alerts
|

Application of Spirulina in aquaculture: a review on wastewater treatment and fish growth

Abstract: There is an urgent need to find alternatives to fish meal and fish oil in compound feeds due to their rapidly rising prices and the demand for sustainable fisheries. Spirulina, a filamentous blue‐green microalga, is an excellent source of plant protein and could replace expensive animal‐derived proteins in fish feed. Studies have evaluated the use of spirulina as a fish meal for different fish species. This paper reviews research on the effects of spirulina on the growth performance of various fish species. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(51 citation statements)
references
References 102 publications
0
51
0
Order By: Relevance
“…Using spirulina as both a dietary supplement and for treatment of effluent for water quality control seems to be an excellent integrated strategy for fish aquaculture (Zhang et al . 2019).…”
Section: Impact Of Spirulina In Aquaculturementioning
confidence: 99%
“…Using spirulina as both a dietary supplement and for treatment of effluent for water quality control seems to be an excellent integrated strategy for fish aquaculture (Zhang et al . 2019).…”
Section: Impact Of Spirulina In Aquaculturementioning
confidence: 99%
“…So, the use of nutritional supplement that could improve the growth performance and fish health would be useful in increasing coloration, resistance to environmental stress and survival rate of fish. Spirulina, Spirulina platensis (SP), is a strain of cyanobacteria (blue‐green algae) that can be used because of nutritional benefits, for example protein, amino acid, vitamins, minerals, essential fatty acid and β‐carotene in aquafeeds (Vonshak, 1997; Zhang et al., 2019). It was reported that dietary supplementation of SP powder could improve growth, lipid digestion, body composition, coloration and intestinal flora of fish (James et al., 2006; Ramakrishnan et al., 2008; Teimouri et al., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Chlorophyll in SP acts as a cleansing and detoxifying factor against toxic substances. As well as, flavour and quality of meat in fish were improved by SP (Zhang et al., 2019). Thus, SP can be an ideal candidate to improve the performance of freshwater ornamental fish species.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, very promising from the national economic and hygienic point of view is soil disposal of wastewater and their use for irrigation of forage and grain crops, which allows increasing water availability, productivity of land and is a powerful means of increasing soil fertility, as well as an effective way of additional treatment in natural conditions [5]. In general, sewage from poultry farms in the republic can irrigate and fertilize 10-12 thousand hectares of land [7]. However, the problem of using wastewater for irrigation of crops requires a regional approach, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In the CIS republics, including the former All-Union Scientific and Production Association VNPO "Progress" (All-Union Scientific Research Institute for Agricultural Crops), Volgograd Agricultural and Ukrainian Hydro-reclamation Institutes, Uzbek Research Institute of Sanitation, Hygiene and Occupational Diseases and other institutions have carried out numerous studies to study the suitability of household and livestock wastewater for irrigation of crops. However, scientific research on the disposal of wastewater from poultry farms has been almost non-existent [5][6][7].…”
Section: Introductionmentioning
confidence: 99%